Phenotypic diversity and performance of agro-nutritional characters in okra germplasm collection from Nigeria - Kolawole, Adesike Oladoyin; Ibitoye, Dorcas Olubumi; Aderibigbe, Olaide Ruth (Journal of Tropical Agriculture, 2023)
Phenotypic characterization of 29 okra accessions kept in the National Horticultural Research Institute gene bank was done along with a local check variety. The study assessed the magnitude of variability in the agronomic traits, nutritional and physicochemical properties of okra accessions. The experiment was carried out at the Teaching and Research Farm of Ladoke Akintola University of Technology, Ogbomoso, in the derived savanna agro-ecology of Nigeriain a 6×5 alpha lattice designs replicated three times. The analysis of variance showed highly significant (P< 0.001) differences for 22 characters, and the results confirms the okra accessions as potential source of nutrients. Fruit weight per plot ranged from 27.2 g to 1893.1 g and showed a positive significant correlation with leaf length (r = 0.47), leaf width (r = 0.48), fruit width (r = 0.26), and number of fruits per plant (r = 0.62). Principal component analysis showed that the first nine components had eigenvalues >1 and explained 81.73 % of the total variation among the okra accessions. Cluster analysis grouped the accessions into three major clusters. The phenotypic diversity observed in this study may be exploited in the selection of parental lines for hybridization when breeding okra for yield and nutritional quality.